A liberdade de imprensa vista pelo Supremo Tribunal Federal: análise da ADPF n. 130 - Napolitano, Carlo José [UNESP] (My University, 2011)
The present study aims to present and analyze the ruling of the Brazilian Supreme Court in ADPF 130 (Concentrated constitutional review action, Fundamental Precept Infringement, Argüição de Descumprimento de Preceito Fundamental), proposed by Partido Democrático Trabalhista (PDT), which contests the compatibility of statute 5.250/67 with the Federal Constitution of 1988. This work considers that the judicial ruling is different than the approach taken by the Legislative and Executive powers, arguing that there is, in the Judiciary, a peculiar way for ruling, surrounded by mysteries, rites, secrets, pomp and circunstances unintelligible to layman. To reach the proposed goal, Justice Carlos Brito´s report and opinion on ADPF 130 are analyzed. The choice of giving special attention to this opinion, which favors the declaration of unconstitutionality of the 5.250/67 statute, is justified in that it represents agreement with the allegation of disrespect to the constitutional text, as suggested by the Partido Democrático Trabalhista. The arguments put forth by the presiding Justice on his ruling will also be the object of consideration, as well as some possible consequences of the ruling.

O presente trabalho objetiva apresentar e analisar a decisão do Supremo Tribunal Federal na Argüição de Descumprimento de Preceito Fundamental – ADPF 130, proposta pelo Partido Democrático Trabalhista, que contestou a recepção da Lei 5.250/67 pela Constituição Federal de 1988. Parte-se do pressuposto que os processos decisórios no judiciário diferem dos processos decisórios no âmbito do legislativo e do executivo, entendendo que há, no poder judiciário, um modo peculiar para a tomada de decisões, cercado de segredos, ritos, mistérios, pompa e cerimônia ininteligíveis para leigos. Para cumprir o objetivo proposto, analisar-se-á o relatório e o voto condutor proferido na ação pelo Ministro Carlos Brito. A opção por dar-se especial atenção ao voto favorável à declaração de não recepção da Lei 5.250/97 pela nova ordem jurídica constitucional se justifica, pois representa concordância com a alegação de desrespeito ao texto constitucional, conforme sugerido pelo Partido Democrático Trabalhista. Nesse sentido, analisar-se-ão os argumentos apresentados pelo relator no ato decisório, bem como, apresentar-se-ão algumas possíveis conseqüências decorrentes da decisão.
Keywords: Brazilian Supreme Court; Freedom of expression; ADPF 130; Constitutionality; Fundamental rights; Supremo Tribunal Federal; Liberdade de expressão; ADPF 130; Recepção Constitucional; Direitos fundamentais